HUBUNGAN ANTARA PENGRAJIN BATIK TULIS DAN PENGEPUL BATIK TULIS (Studi di Dusun Tanuraksan, Desa Gemeksekti, Kecamatan Kebumen, Kabupaten Kebumen) - , AKBAR BAHTIAR; , Drs. Soetomo. M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Batik , certainly familiar to hear people today. Famous batik cloth with a unique fabric and has a high price. However, the price of an expensive batik is not necessarily making batik craftsmen to prosperity for granted even be considered earned income is less than adequate. Only about Rp450.000 , 00 are obtained by batik craftsmen each month. Sales of batik batik artisans generally by collectors , so its sales are sometimes much cheaper than the market price. However, looks like batik craftsmen powerless to circumstances and still sell to collectors batik, than this is actually the question arises how the pattern of relationships batik craftsmen and collectors batik ? This research was conducted in the village Tanuraksan, Gemeksekti Village, District Kebumen. This study used a qualitative research method that is based on this study because the want to know how the relationship between batik and batik collectors and the dynamic in the relationship. The theory used is from Karl Marx 's theory of exploitation . Known research results obtained are at least two kinds of relations between batik and batik collectors, the first relationship selling and labor relations with the employer. In this relationship the relationship of exploitation especially apparent in the relationship between workers and employers. In connection made batik batik bound by collectors by providing raw materials to the artisans batik freely , but of the batik makers must sell back the results to the collectors batik cloth batik. The existence makes it difficult to develop because the craftsmen can not market their products directly to consumers who have a higher price than selling back to collectors batik.